Desain Insinerator Tipe TEP-1 - Asmara, Sandi; Jati, Dhanur Pramono; Kuncoro, Sapto; Warji, Warji (abe.fp.unila.ac.id, 2024)
The waste problem in Bandar Lampung is becoming increasingly critical as the volume of domestic waste reaches 1,283 tons per day. Ineffective management can lead to negative impacts on public health and the environment, such as the spread of diseases and pollution. This study aims to design and test a household-scale incinerator that is effective, efficient, safe, and low in pollution as an alternative solution for waste management. The designed incinerator is capable of burning 30 kg of waste in 180 minutes, using a fuel mixture of used oil and gasoline amounting to 130 ml. Test results show that the thermal efficiency of the incinerator ranges from 70-75%, with a charcoal yield of 14.42% and an ash yield of 11.53%. The overall efficiency reaches 77.05%, indicating that this device can optimally utilize the energy produced from combustion. This research demonstrates that a household-scale incinerator can be an effective solution for reducing waste volume and minimizing negative impacts on the environment. Recommendations for future research include the development of the incinerator design, evaluation of the temperature control system, and analysis of emissions generated from various types and compositions of waste. Thus, this study makes an important contribution to more environmentally friendly and sustainable waste management in Indonesia. Keywords: Combustion, Development, Design, Incinerator, Waste, Used Oil, Yield.